RESPONSIVITAS PENANGANAN PENGADUAN CEPAT RESPON MASYARAKAT DI PROVINSI DKI JAKARTA - Hafiza Islami, Hasna; Zarkasyi Rahman, Amni; Hanani, Retna (Journal of Public Policy and Management Review, 2024)
The DKI Jakarta Provincial Government's complaint channel called Cepat Respon Masyarakat (CRM) has successfully resolved 953,623 public complaints with a resolution of 93.45% since 2016. The high volume of public complaints in DKI Jakarta, which reaches hundreds of thousands every year, shows the urgent need for an efficient complaint management system through the Cepat Respon Masyarakat service. One of the CRM complaint handling is carried out by the Government Bureau through the Expert Facilitator who is tasked with verifying and validating the results of the complaint follow-up. This study aims to analyze the responsiveness and factors that influence the responsiveness of Expert Facilitators in the implementation of CRM complaint handling. This research uses descriptive qualitative methods with data collection techniques of interviews, observation, and documentation. The responsiveness of Expert Facilitators is seen based on the phenomenon of the attitude of bureaucratic apparatus in responding to complaints and service users in Agus Dwiyanto's responsiveness theory (2006). The results showed that the responsiveness of the Expert Facilitator was still found lacking due to the low knowledge of the Expert Facilitator regarding the regulations used in responding to complaints and the mechanism for disseminating service information carried out by the Expert Facilitator had not been conveyed to the community as a whole. Internal factors that affect the responsiveness of Expert Facilitators consist of: background work experience of Expert Facilitators and open communication between the Government Bureau and Expert Facilitators. While external factors that affect the responsiveness of the Expert Facilitator include: the condition of the CRM complaint handling server, community behavior, government cooperation, and environmental conditions.